0524 Web-Delivered CBT for Insomnia Intervention Improves Sleep Among Adults with Insomnia and Depressive Symptoms. (27th May 2020) - Batterham, P J; Christensen, H; Thorndike, F P; Ritterband, L M; Gerwien, R; Enman, N; Botbyl, J; Maricich, Y
Abstract: Introduction: Cognitive behavioral therapy for insomnia (CBT-I) is the first line recommended treatment for adults with chronic insomnia. In a prior randomized controlled trial (RCT), data showed web-delivered CBT-I (SHUTi) reduced insomnia severity as well as symptoms of depression, among adults with insomnia and elevated depressive symptoms. The present study aimed to further evaluate the effectiveness of web CBT-I to improve sleep outcomes as measured by prospectively entered sleep diaries in this same sample. Methods: A large-scale RCT (N=1149) of Australian adults with insomnia and depressive symptoms compared a 9-week, web CBT-I therapeutic with an attention-matched web program at baseline, posttest and 6-, 12-, and 18-month follow-ups. Although depression outcomes have been presented previously, the online sleep-diary derived variables have not yet been presented, including sleep-onset latency (SOL), wake after sleep onset (WASO), sleep efficiency (SE), number of awakenings, sleep quality, and total sleep time (TST). Sleep diaries were entered online for 10 days at each assessment period. Results: Data showed web CBT-I participants demonstrated greater reductions from baseline to posttest compared with control for the following sleep variables: SOL (LS mean difference [95% CI]=-22.3 min [-29.2, -15.3]; p<.0001), WASO (-17.8 min [-23.4, -12.3]; p<.0001), and number of awakenings (-0.38 [-0.68, -0.09]; p=.0113). Web CBT-I also showed greater improvements in SE (9.18% [7.25%, 11.10%]; p<.0001) and sleep quality (0.41 [0.30, 0.53]; p<.0001) from baseline to posttest compared with control. TST was not significantly different between groups at posttest or 6-month follow-up, although it improved over baseline at 12 (18.73 min [7.39, 30.07]; p=.0013) and 18 months (23.76 min [9.15, 38.36]; p=.0015) relative to control. All other significant sleep treatment effects were maintained in the treatment arm at 6, 12, and 18-month follow-up. Conclusion: Data showed web CBT-I produced lasting improvements in sleep outcomes among adults with insomnia and elevated depressive symptoms. Support: Clinical trial ACTRN12611000121965 was funded by the Australian National Health and Medical Research Council. The statistical analysis described here was funded by Pear Therapeutics, Inc and conducted by Provonix.